Pengaruh Pertumbuhan Asuransi Syariah terhadap Pertumbuhan Ekonomi Indonesia - Dedy Mainata; Angrum Pratiwi (International Journal Ihya' 'Ulum al-Din, 2019)
This study aims to determine the effect of growth in Islamic insurance on economic growth. By using secondary data sources, secondary data in the form of total Islamic insurance assets during 2015-2017 originated from the report of the Non Islamic Bank Financial Industry in the official website. This study analyzes the influence of the growth variables of Islamic insurance on economic growth. With the Independent variable in this study is the growth of Islamic insurance with total assets as an indicator (X). And the dependent variable in this study is Indonesia's economic growth using the indicator Gross Domestic Product (GDP) or Gross Domestic Product (GDP) (Y). The results of the study show that the growth variables of Islamic insurance have an effect on Indonesia's economic growth.